2014
DOI: 10.1016/j.diabet.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose-lowering agents on vascular outcomes in type 2 diabetes: A critical reappraisal

Abstract: Type 2 diabetes mellitus is strongly associated with cardiovascular complications, especially coronary artery disease. Numerous epidemiological studies showed a close relationship between major cardiovascular events and glycaemia and several pathophysiological mechanisms have been described that explain how hyperglycaemia induces vascular damages. However, randomized controlled trials that investigated either an intensive glucose lowering strategy versus standard care or the addition of a new glucose-lowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 82 publications
(100 reference statements)
0
19
1
3
Order By: Relevance
“…These impressive results strongly contrast with several disappointing results previously reported with other glucose-lowering agents in T2D [6], and are also more favourable than those reported with metformin in high-risk populations [7]. A recent systematic review and meta-analysis suggested that results for other SGLT2 inhibitors (specifically, canagliflozin and dapagliflozin) may not be clearly different, although results from ongoing studies will be crucial for substantiating these findings across the drug class [8].…”
Section: Introductioncontrasting
confidence: 67%
“…These impressive results strongly contrast with several disappointing results previously reported with other glucose-lowering agents in T2D [6], and are also more favourable than those reported with metformin in high-risk populations [7]. A recent systematic review and meta-analysis suggested that results for other SGLT2 inhibitors (specifically, canagliflozin and dapagliflozin) may not be clearly different, although results from ongoing studies will be crucial for substantiating these findings across the drug class [8].…”
Section: Introductioncontrasting
confidence: 67%
“…Past history of cardiovascular disease or congestive heart failure may represent a key criterion of choice considering the remarkable efficacy of the SGLT2i empagliflozin in EMPA-REG OUTCOME [11,12], contrasting with previous mitigated results reported with other glucose-lowering agents, including DPP-4i [61]. Thus, in clinical practice, the choice should be individualized according to individual characteristics of the patient [62].…”
Section: Expert Opinionmentioning
confidence: 82%
“…After the UKPDS [5], most CV outcome trials with glucose-lowering agents gave rather disappointing results [15][16][17][18]. Dipeptidyl peptidase-4 inhibitors (gliptins), which exert almost a neutral effect on BP [19], proved non-inferiority but no superiority versus placebo, demonstrating the CV safety of this pharmacological class but not its efficacy in preventing CV events [20].…”
Section: Introductionmentioning
confidence: 99%